What Could Wild Life Be? Etho-ethnographic Fables on Human-Animal Kinship. Issue 1 (2nd January 2020) - Vannini, Phillip; Vannini, April
Abstract : Can humans and wild life co-exist? Drawing from ethnographic fieldwork conducted in and nearby Waterton Lakes National Park and Banff National Park, Alberta, Canada, we present two etho-ethnographic fables that show how a positive coexistence of humans and wild life may be sought after and achieved. The two stories–narrated by animals' voices–prompt us to rethink the very meanings of wild life and humanity and challenge us to envision and appreciate a new kind of affective relationship between people and non-human animals. By attending to the mutual trust and care inherent in respect-based multi-species entanglements, in this article we attune ourselves to the importance of the relational autonomy of wild animals and generate ideas on what wild life could be when understood from the perspective of relational and Indigenous ontologies.